Nano‐spaced Gold on Glassy Carbon Substrate for Controlling Cell Behavior. Issue 11 (19th April 2020) - Chauhan, Gaurav; Ángeles, Alejandro Lujambio; Gonzalez‐González, Everardo; Kulkarni, Manish M.; Cardenas‐Benitez, Braulio; Jiménez, Martín Francisco; Trujillo‐de Santiago, Grissel; Alvarez, Mario M.; Madou, Marc; Martinez‐Chapa, Sergio O.
Abstract: This approach involves the synthesis of gold nanoparticles (GNPs) within the carbonizing photoresist (SU8) to achieve GNPs trapped glassy carbon (GNPs‐GC) substrates. Surface size distribution and interparticle separation of GNPs is primarily controlled by changing the metal precursor concentration. Chemical stability and fabrication control are achieved by selecting sodium tetrachloroaurate (NaAuCl4 ) over a more conventional aurochloric acid (HAuCl4 ) as the gold precursor. Seeding of gold nuclei in a photocrosslinking polymer is a classical representation of simultaneous homogeneous and heterogeneous nucleation. GNPs growth during the carbonization process is tracked and explained using pertinent mechanisms. With the nanoparticle spacing ranging from 260 to 50 nm, GNPs‐GC thin films are employed as interfaces for fibroblast cell adhesion. GNPs act as potential anchor points for cell adhesion and their nanoscale arrangement regulates the structural behavior of the cells. GNPs' density‐dependent fibronectin physisorption significantly improves cell adhesion and proliferation. Intraparticle spacing around 160 nm offers ideal biointerface for fibroblast attachment and spreading. Fabrication of 3D GNPs composite carbon microelectromechanical systems is achieved as a demonstration of the studied GNPs‐GC synthesis mechanism. Sub‐micron patterning of GNPs‐GC combined with its biofunctional nature presents vast opportunities in the field of bioelectronics, biophotonics, and lab/organ‐on‐a‐chip technology. Abstract : Fabrication of glassy carbon substrates with surface nano‐spaced gold nanoparticles (GNPs) using a simple and scalable process. Gold is nucleated in a photocrosslinking polymer and grown into nanoparticles during carbonization. Process is stabilized and controlled for lithographical patterning of 3D features or MEMS. Cell–material interaction studies on the resultant surfaces revealed the effect of interparticle spacing of GNPs on cell behavior.